The poems and psalms of the Hebrew Bible - Gillingham, S. E. (Susan E.) (Oxford Bible series., 1994)
Because of the command not to make 'graven images', the creativity of the ancient Jews was always somewhat constrained: instead of the visual arts, poetry and story became the two most important forms which depicted the relationship between God and his people. This book concentrates on the poetry of the Hebrew Bible. After considering the essential elements of Hebrew verse, it looks at the most familiar poems - the Psalms, the Song of Solomon, and the poetry in Job and Proverbs - as well as at less familiar examples of poems which by contrast are embedded in narrative such as war poetry, harvest hymns, elegies, prayers of protest, and thanksgiving songs. It is notoriously difficult to ascertain whether a poem has been composed for a real-life setting - whether to do with worship or with everyday affairs - or whether it has been written as a purely literary artefact. This study proposes that, although these biblical poems should be understood primarily as ancient literary texts, many also have a setting in life beyond the text, offering us a broader framework of reference on account of their pre-literary history. This is written for those who already have some grounding in the contents of the Hebrew Bible, but it is also designed to be read by non-specialists, and no knowledge of Hebrew is presumed. A select bibliography following each chapter offers suggestions for further reading.